Assessment of Water Quality, Fish Population Health, and Plankton Dynamics in River Yobe, Nigeria: Implications for Fishery Productivity - Badejo, Binta Ibrahim; Waru, Hadiza Zumami; Cheri, Ali Muhammed (FUDMA Journal of Sciences, 2026)
This study assessed the ecological status of River Yobe, Nigeria, by evaluating its physicochemical water quality, the health of two key fish species (Oreochromis niloticus and Clarias gariepinus), and the structure of plankton communities across three sites with varying anthropogenic pressures. Water and biological samples were collected monthly over an 18-month period (November 2021 – April 2023). Physicochemical analysis revealed significant seasonal variations; while key parameters like temperature (19.41–29.48°C), pH (5.57–7.71), and dissolved oxygen (2.60–13.67 mg/L) were generally within acceptable ranges, elevated ammonia (up to 0.927 mg/L) and nitrate (up to 0.930 mg/L) levels indicated nutrient loading from agricultural runoff and domestic waste. Length-weight relationship analysis showed negative allometric growth (b < 3) for both fish species, with condition factors ranging from 0.65–4.24 for O. niloticus and 0.82–4.15 for C. gariepinus, reflecting fluctuating wellbeing linked to environmental stress. Plankton analysis identified 17 phytoplankton and 16 zooplankton species, with Chlorophyceae (Cladophora oligoclonus) and Rotifera (Branchionus sp.) dominating, respectively. Highest plankton abundance was recorded at sites with the most intense anthropogenic activities, correlating with elevated nutrient levels. The study concludes that while River Yobe's basic water quality supports aquatic life, it is under significant stress from anthropogenic eutrophication, which impacts fish health and drives shifts in plankton communities, underscoring the need for integrated watershed management for long-term fishery sustainability.
Keywords: Plankton; Dynamics; Population; Health